ANALISIS PERSEPSI MANFAAT APLIKASI E-BUPOT UNIFIKASI PADA INSTANSI PEMERINTAH - Ibnu Yudhi Wibowo; Dahlia Sari (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2023)
This research was motivated by the release of e-Bupot Unifikasi application for government agency taxpayers in September 2021. Unlike the previous application, this application combines all applications for making withholding and tax reporting. This study aims to analyze the perceived benefits of e-Bupot Unifikasi application by Government Agencies registered at KPP Pratama Jakarta Kramat Jati and its effect on tax compliance using the Technology Acceptance Model, the Information System Success Model (ISSM) and instrumental perspective compliance. This study used a quantitative method with descriptive statistics and multivariate analysis using SmartPLS3. Data collected by questionnaire technique. Respondents were 51 Government Agency Taxpayers registered at KPP Pratama Kramat Jati. Results showed that perceived usefulness and perceived ease of use had a significant positive effect on perceived net benefits from using e-Bupot Unification application. Both perceptions are influenced by several attributes of application quality in the ISSM. Perceived net benefits have a significant positive effect on tax compliance. However, tax compliance in terms of timely submission by respondents has not increased significantly with the release of e-Bupot Unifikasi application.